2015
DOI: 10.1016/j.polymertesting.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrocarbon ageing on the mechanical properties, apparent crosslink density and CO2 diffusion of a hydrogenated nitrile butadiene rubber (HNBR)

Abstract: a b s t r a c tThe effect of ageing in a sweet oil environment on the tensile properties, apparent crosslink density, CO 2 diffusion and Shore hardness of a typical carbon black reinforced hydrogenated nitrile butadiene rubber (HNBR) is presented. Different ageing conditions yielded materials with different properties, attributed to varying degrees of apparent crosslinking. These results showed that, with increasing apparent crosslink density, tensile stiffness and hardness increased, while CO 2 diffusivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 36 publications
(25 reference statements)
1
32
1
Order By: Relevance
“…One reason for the lower leakage rates after 98 days of ageing can be the better adaption of the rubber to the roughness of the seal face with the influence of time and temperature. Additionally, the rather strong decrease of leakage rate of HNBR with ageing can be explained by crosslinking occurring during ageing, leading to reduced permeation of gas molecules through the material …”
Section: Resultsmentioning
confidence: 99%
“…One reason for the lower leakage rates after 98 days of ageing can be the better adaption of the rubber to the roughness of the seal face with the influence of time and temperature. Additionally, the rather strong decrease of leakage rate of HNBR with ageing can be explained by crosslinking occurring during ageing, leading to reduced permeation of gas molecules through the material …”
Section: Resultsmentioning
confidence: 99%
“…The composition is shown in Table 1 and is based on hydrogenated nitrile butadiene rubber (HNBR) with 96 % saturated butadiene units with 36% acrylonitrile content. This HNBR was selected because previous work showed that it has a combination of good ageing resistance, hydrocarbon resistance [28], necessary barrier property [28,29] and some low-temperature flexibility. The compound formulation did not contain carbon black, in order to elucidate the pure effect of zirconium tungstate without having interaction effects coming from carbon black; only necessary additives and processing aids were present.…”
Section: Materials and Processingmentioning
confidence: 99%
“…As with all polymers, HNBR shows changes in structure and mechanical performance over time in service, depending on factors such as the local chemical environment and temperature, and previous works have described some of these changes [38,39]. However, all the tests reported in this paper were performed on materials in an unaged state, i.e.…”
Section: Introductionmentioning
confidence: 99%